Mitigating anti-microbial resistance in the environment: A one health governance analysis in Kenya - Srinivasa Reddy Srigiri; Morris Buliva (German Institute of Development and Sustainability (IDOS), 2025)
Antimicrobial resistance (AMR) poses a critical threat to global health, with environmental transmission pathways - pharmaceutical waste, wastewater effluents, agricultural runoff - increasingly recognised as significant yet inadequately governed. Despite international calls for One Health approaches integrating human, animal and environmental sectors, coordination across these domains remains weak, particularly for environmental dimensions. This paper examines why environmental integration lags in Kenya's AMR governance, despite sophisticated formal architecture that includes national and county coordination platforms (NASIC, CASICs), technical working groups and the One Health AMR Surveillance System (OHAMRS). We investigate two research questions: (i) What are the enablers and barriers to effective governance of interlinkages among human health, animal health and environmental sectors in mitigating AMR? (ii) What are the options for effectively integrating the environmental dimension into AMR governance? Drawing on polycentric governance theory, the Institutional Analysis and Development (IAD) framework and the concept of Networks of Adjacent Action Situations (NAAS), we analyse how authority, information and resources shape interactions among overlapping decision centres across constitutional, collective-choice and operational levels. Through 12 semi-structured interviews with government officials, fisheries officers and environmental regulators, supplemented by policy document analysis, we map six action situations spanning planning, resource allocation, surveillance, stewardship, wastewater treatment and regulation. Findings reveal that constitutional-choice rules create formal overlaps intended to foster coordination, yet systematic asymmetries in authority, information and resources perpetuate the marginalisation of environmental issues. Boundary and position rules concentrate agenda setting in health sectors; information rules exclude AMR parameters from environmental permits and inspections; payoff rules reward clinical outputs while environmental investments compete with higher priorities; and scope rules omit environmental accountability targets. These rule configurations attenuate feedback loops between environmental action situations and upstream planning, maintaining system stability but at sub-optimal performance for One Health objectives. We identify rule-focused interventions - mandating environmental representation with voting authority, embedding AMR parameters in regulatory instruments, institutionalising joint inspection protocols, ring-fencing environmental budgets, and establishing explicit environmental targets - that would realign coordination toward genuine environmental integration.
Keywords: 320; One Health; Antimicrobial Resistance; Polycentric Governance; Coordination; Environmental Health; Action situations; Institutions